Crowdfunding to Finance SMEs: New Model After Pandemic Disease - Marina, Anna; Imam Wahjono, Sentot; Fam, Soo-Fen; Rasulong, Ismail (The Indonesian Forestry Certification Cooperation, 2023)
The purpose of this paper is to find out the success of crowdfunding in finance SMEs (Small and Medium Enterprises) and business startups during and after the Corona Virus Pandemic (Covid19) in Indonesia and Malaysia. Methodology - This research uses a quantitative approach. The questionnaire was distributed to SMEs owners or operators who already knew about crowdfunding domiciled in Indonesia and Malaysia, each country as many as 100 respondents. To find out the influence and significance of Crowdfunding perception, Social norms, Regulation, Entrepreneurship and Technology, and Capital Market on the success of Crowdfunding by using multiple linear regression analysis. Finding – in Indonesia, of the 5 variables studied all showed positive and significant influences with levels of influence varying from weak to medium correlations, except perception variables that showed weak and insignificant influences. In Malaysia, all variables have a positive and significant influence on the level of influence from weak to moderate correlation. Limitation – this study was conducted in Indonesia and Malaysia during the pandemic period with policies on social distancing, physical distancing, and work from home. Originality – This is the first paper to report research on the impact of Corona virus on crowdfunding in Indonesia and Malaysia.